2007
DOI: 10.1200/jco.2007.25.18_suppl.9101
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of painful osseous metastases: A multicenter trial: American College of Radiology Imaging Network 6661

Abstract: 9101 Background: Radiofrequency Ablation (RFA) can destroy tissue in a defined area. Single institutions have reported that RFA can reduce pain from bone metastases. To confirm this, the American College of Radiology Imaging Network (ACRIN) completed a multicenter study of RFA for bone metastases. Methods: Eligible patients had bone pain in one dominant site: tumor size < 8 cm, and location > 1 cm from the spinal cord or cauda equina. RFA was performed under CT guidance. The Memorial Pain Assessment Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 0 publications
2
59
0
4
Order By: Relevance
“…RF ablation of bone lesions has proven successful in pain management, especially for those who do not attain adequate analgesia without intolerable effects. [232][233][234][235] Several small studies have also demonstrated the palliative effects of high-intensity focused ultrasound (HIFU) treatment of bone lesions. [236][237][238] Physical and occupational therapy may also be beneficial in the prevention of complications associated with SREs.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
See 1 more Smart Citation
“…RF ablation of bone lesions has proven successful in pain management, especially for those who do not attain adequate analgesia without intolerable effects. [232][233][234][235] Several small studies have also demonstrated the palliative effects of high-intensity focused ultrasound (HIFU) treatment of bone lesions. [236][237][238] Physical and occupational therapy may also be beneficial in the prevention of complications associated with SREs.…”
Section: Management Of Bone Pain Without An Oncologic Emergencymentioning
confidence: 99%
“…Ablation therapy (eg, RF ablation, ultrasound ablation) for bone lesions can also be helpful in reducing pain. [232][233][234][235][236][237][238] See "Management Strategies for Specific Cancer Pain Syndromes, Bone Pain Without an Oncologic Emergency" (PAIN-D, page 980) for more information.…”
Section: Interventional Strategiesmentioning
confidence: 99%
“…The patient selection criteria are similar to those using SBRT. RFA is effective in reducing pain resulting from skeletal metastatic disease, as demonstrated in two multicentric trials [60,61], even though the results of the two studies are different because of factors that include patient selection, the level of anesthesia, and the degree of tumor destruction. At the 3-month time point, there was a reduction in pain of 14 points in the American College of Radiology Imaging Network study and of 28 points in the Goetz et al…”
Section: Spinal Metastasesmentioning
confidence: 99%
“…Percutaneous tumor ablation is recommended for pain palliation when radiation therapy cannot be offered or is incompletely effective (grade C) [12,13,15,34,[48][49][50][51][52][53]. In a retrospective study of 128 radiofrequency-ablated spinal metastases, patients reported a mean preprocedure pain score of 7.51/10 6 2.46 and decreased mean pain scores 1 week (1.73/10 6 2.28; p , .0001), 1 month (2.25/10 6 2.44; p , .0001), and 6 months (1.75/10 6 2.62; p 5 .009) after treatment [15].…”
Section: Uncomplicated Painful Spinal Metastasesmentioning
confidence: 99%